An Examination of Nutritional Approaches and Stress Levels in Athletes: Nutritional approach and stress - Tutkun, Erkut (Progress in Nutrition, 2020)
For athletes, nutrition is very important not only for sporting success but also with regard to health. The aim of this study is to determine nutritional approaches and stress levels in athletes. A total of 420 athletes aged 17-24, studying at Ondokuz Mayıs University, took part in the study. The participants’ BMI was calculated from their age, height and body weight, and a nutritional approach test questionnaire and perceived stress scale were applied. For the statistical evaluation, student t-test, one-way variance analysis and LSD tests were used. The average ages of the students were 22.13 for females and 22.85 for males. BMIs were determined as 22.00 kg/m2 for females and 24.15 kg/m2 for males. Nutrition scores were calculated as 16.49 for females and 18.06 for males. In the nutrition questionnaire, according to the gender of the students evaluated, no statistically significant difference was determined among ages (p>0.05), whereas statistically significant differences were determined among heights, body weights and BMI values (p0.05), the total score distributions in the nutritional approach test were found to be statistically significant according to BMI (p